A High Frequency Transformer Isolation Ups System With 110V/220V Input Voltage - Torrico-Bascopé, René P.; Oliveira Jr., Demercil S.; Branco, Carlos G. C.; Antunes, Fernando L. M. (Eletrônica de Potência, 2006)
This work proposes an isolated double conversion UPS with power factor correction using a high frequency transformer, and input voltages equal to 110V/220V. The arrangement is suitable to rack structures because it has small size and reduced weight. For both input voltages, the proposed converter has almost the same efficiency processing the same output power. Other relevant features are soft commutation of the controlled switches in the chopper and the boost stage, simple control strategy that can be implemented with well-known integrated circuits, and the use of few batteries in series due to the step-up stage. Qualitative analysis and experimental results obtained from 2kVA laboratory prototype are presented.